Evaluating the Impact of Emerging Technologies on Mobile User Experience: The Role of User-Centered Design in Overcoming Development Challenges - Fazil, Abdul Wajid; Hamidi, Shir Ahmad; Habibi, Habibrahman (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The adoption of emerging technologies, namely Artificial Intelligence (AI), Augmented Reality (AR), Virtual Reality (VR), 5G and the Internet of Things (IoT), has far-reaching implications for mobile user experience (UX) and this study enhances current research by evaluating the effectiveness of adopting user-centered design (UCD) methodologies to address emerging technologies for mobile experiences. The mixed-methods framework involves both quantitative survey and qualitative interviews to deliver a holistic perspective. The survey focuses on industry professionals and mobile app users to assess how they view AI's role in making personalization part and parcel of the experience, AR/VR role in enabling immersion and engagement, and any challenges presented by device screen size and varied user needs. In addition, semi-structured interviews provide qualitative data that reveal human insight into how practical work is influenced and the practices of design. The study shows AI makes an application much more personalized compared to AR & VR which provide an immersive rich experience but can have technical difficulty with implementation. The research underscores the importance of UCD in enhancing mobile applications and emphasizes the need for iterative design processes along with continual feedback from users to overcome developmental challenges. Moreover, there is a consensus that UX success and ongoing upgrades can be measured via qualitative metrics like user retention rates and satisfaction surveys. This study highlights the growing importance of combining advanced technology with effective design methodology to keep up with shifting user expectations and to improve the competitiveness of mobile apps